Residue-Level Contact Reveals Modular Domain Interactions of PICK1 Are Driven by Both Electrostatic and Hydrophobic Forces - Stevens, Amy O.; He, Yi (Frontiers in Molecular Biosciences, 2021)
PICK1 is a multi-domain scaffolding protein that is uniquely comprised of both a PDZ domain and a BAR domain. While previous experiments have shown that the PDZ domain positively regulates the BAR domain and the C-terminus negatively regulates the BAR domain, the details of internal reguation mechanisms are unknown. Molecular dynamics (MD) simulations have proven to be a useful tool in revealing the atomic-level resolution of intramolecular interactions. PICK1 performs its biological functions in a dimeric form which is extremely computationally demanding to simulate with an all-atom force field. Here, we use coarse-grained MD simulations to expose the key residues and driving forces in the internal regulations of PICK1. While the PDZ and BAR domains do not form a stable complex, our simulations show that the PDZ domain most probably interacts with certain regions of the concave surface of the BAR domain. Furthermore, our results reveal that it is the surface of both the binding pocket and the βB-βC loop of the PDZ domain that form such interactions with the BAR domain. Their interactions are driven by both electrostatic and hydrophobic forces. In contrast, our simulations reveal a very dynamic C-terminal that most often resides on the convex surface of the BAR domain rather than the previously suspected concave surface.